Synergy of Religion and Customs in the Muslim Community of Pegayaman Village, Bali - Faizah, Rohmatul; Yusrina, Jihan Avie (Future Science, 2023)
Religion is a sensitive issue that is easily brought up in Indonesia's pluralistic society. Moreover, minority groups sometimes feel they have less freedom of movement amidst various clashes with the customs and traditions of the majority. The dynamics between religion and custom must be addressed wisely and judiciously by all elements of society to form a harmonious, peaceful life in a pluralistic society. This requires sensitivity between religious communities to tolerate each other's customs and traditions without sacrificing their own beliefs. So, there will be excellent synergy between religion and custom. Conditions like this can be found in the Muslim community of the Balinese Pegayaman village, whose position is a minority but can integrate with local regional customs which are very strongly Hindu. This form of synergy between religion and customs in Muslim society in Bali is very interesting to research, as an example for a pluralistic society as well as a means of introducing customs and traditions through scientific publications. It turns out that the key to the synergy between religion and custom that is very well formed lies in the emotional sensitivity to respect and love each other and maintain traditions by internalizing religious values. This can be seen in the unique naming of the Muslim community, where they add family names according to Balinese traditions such as Wayan, Putu, Gede in front of their names which have Islamic nuances.